Analisis Faktor Human Error terhadap Peluang Terjadinya Kecelakaan pada Pengemudi Bus Menggunakan Pendekatan Human Factors Analysis and Classification System - Eva Nursifa Fauziah Suwandi; Bambang Suhardi; Etika Muslimah (Dinasti Research, 2026)
Bus accidents remain one of the major road transportation safety issues in Indonesia, with human factors being the dominant cause of traffic accidents. Antar Kota Antar Provinsi (AKAP) and Antar Kota Dalam Provinsi (AKDP) bus drivers face various operational conditions that may lead to human error and increase the risk of accidents. Therefore, it is necessary to identify the human error factors that contribute to accidents to support efforts to improve bus transportation safety. This study aims to identify human error factors based on the Human Factors Analysis and Classification System (HFACS) framework and to analyze the influence of these factors on the likelihood of accidents among bus drivers. This study employed a quantitative approach involving 85 AKAP and AKDP bus drivers at Tirtonadi Terminal. Data was collected using an HFACS-based questionnaire covering four levels: Unsafe Acts, Preconditions for Unsafe Acts, Unsafe Supervision, and Organizational Influences. Construct validity was assessed using Exploratory Factor Analysis (EFA), reliability was tested using Cronbach’s Alpha, and the influence of the factors was analyzed using binary logistic regression. The EFA results showed that the research instrument formed four factors consistent with the HFACS framework, with 18 items meeting the validity and reliability criteria. The logistic regression results indicated that the Unsafe Acts factor had a significant effect on bus drivers’ accident history (p = 0.025), whereas the Preconditions for Unsafe Acts, Unsafe Supervision, and Organizational Influences factors did not have a significant effect. These findings suggest that factors related to drivers’ actions and behaviors while driving contribute the most to accident risk. The results of this study are expected to serve as a basis for bus operators and regulators in developing strategies to improve bus operational safety.